2014
DOI: 10.1007/s00408-014-9670-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dexamethasone and Oxygen in Ventilated Adult Sheep with Early Phase Acute Respiratory Distress Syndrome

Abstract: Our study showed that corticosteroids did not influence inflammation in early phase ARDS and that hyperoxia aggravated lung injury which could not be modulated by dexamethasone in early phase ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
2
12
1
Order By: Relevance
“…Nevertheless, our findings are in conflict with another very similar study, where systemic dexamethasone did not have any effect on clinic parameters and lung injury (Engel et al 2015). The discrepancy may be related to different experimental animals used in these studies and varied lung lavage and treatment protocol.…”
Section: Nt Tbarscontrasting
confidence: 99%
“…Nevertheless, our findings are in conflict with another very similar study, where systemic dexamethasone did not have any effect on clinic parameters and lung injury (Engel et al 2015). The discrepancy may be related to different experimental animals used in these studies and varied lung lavage and treatment protocol.…”
Section: Nt Tbarscontrasting
confidence: 99%
“…One of the most studied therapy has been systemic corticosteroids. Clinical trials on ARDS patients and subsequent meta analyses (Steinberg et al ; Foster ; Yehya et al ; Meduri et al ; Kimura et al ; Tongyoo et al ; Standiford and Ward ; Yang et al ; Fan et al ) as well as experimental studies in animal models of acute lung injury (ALI) (Chen et al ; Leite‐Junior et al ; Wang et al ; Xu et al ; Yubero et al ; Hegeman et al ; Engel et al ) have indicated that glucocorticoids (e.g., methylprednisolone, dexamethasone, hydrocortisone) elicit variable effects as a function of the dose, the route of administration, the time to treatment initiation and duration, the age of the patient, the cause of ARDS/type of ALI model and/or the measured outcomes. Therefore, the available evidence for glucocorticoids benefits in ARDS is conflicting and the use of these treatments in ARDS patients are still subject to debate (Bein et al ; Bihari et al ; Seam and Suffredini ; Thompson and Ranieri ; Mac and McAuley ; Meduri and Siemieniuk ; Bos et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma from blood samples were collected every 30 min, spun down and stored at -80ºC. After four hours, the animals were euthanized by an intravenous injection of thiopental (18,19). Thoracotomy was performed and the lungs were removed.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…As markers of gas exchange, OI and VEI were calculated from the cardio-respiratory parameters and blood gas analyses before and after lavage, and every 30 minutes during the 4-hour study period (18,19 (20). This was used as marker for in ammation.…”
Section: Experimental Protocolmentioning
confidence: 99%